PERFORMA AYAM KUB (KAMPUNG UNGGUL BALITNAK) PERIODE GROWER PADA PEMBERIAN RANSUM DENGAN KADAR PROTEIN KASAR YANG BERBEDA - Sari, Made Lupita; Tantalo, Syahrio; Nova, Khaira (Jurnal Riset dan Inovasi Peternakan, 2017)
The aims of research  to know the effect of the different crude protein ration to the performance of KUB chicken.  The research was conducted in July to August 2017 in the poultry cage Integrated Field Laboratory, Agriculture Faculty, University of Lampung.  The chicken used in this research were 95 chicken at the age of 4--8 weeks old.  Trial design that used is Completely Randomized Design (CRD) with 3 treatments and 8replications.  Every trial unit consist of 4 KUB chickens.  The treatment is used  the ration with the crude protein of P0 : 15,60%; P1 : 12,81%; P2 : 10,05%.  The data obtained were analyzed using the analysis of variant of 5% level and continued with the BNT test.  The observed variables were the feed consumption, protein consumption, body weight gain, feed conversion, and income over feed cost.  The results showed that the different crude protein ration was not significant (P>0,05) on feed consumption, protein consumption, body weight gain, feed conversion, and income over feed cost of KUB chicken grower phase. Keywords: Performance, Kampung Unggul Balitak (KUB) chicken, rations and crude protein.